Marlborough England's fragile genius - Holmes, Richard 1946-2011 (HarperPress, 2008)
SCOTT (copy 1): Missing title page.
Keywords: Marlborough, John Churchill / Duke of / 1650-1722; Marlborough, John Churchill <Duke of, 1650-1722>; Marlborough, John Churchill of -- 1650-1722; Geschichte 1700-1800; Statesmen / Great Britain / Biography; Generals / Great Britain / Biography; Geschichte; Politik; Generals -- Great Britain -- Biography; Statesmen -- Great Britain -- Biography; Great Britain / History / 1660-1714; Great Britain / History, Military / 18th century; Großbritannien; Great Britain -- Court and courtiers -- Biography; Great Britain -- History -- 1660-1714 -- Biography; Great Britain -- History, Military -- 18th century; Great Britain -- Politics and government -- 1660-1714; Biografie